DEVELOPMENT OF E -MODULE IN ACID BASE MATERIALS GUIDED INQUIRY LEARNING BASED ON IMPROVING STUDENTS' LEARNING MOTIVATION - Okta, Nadya; Fatayah, Fatayah (Universitas Negeri Surabaya, 2024)
The purpose of this tstudy (1) to determine the validity of the chemistry e-module based on Guided Inquiry Learning (2) to determine the increase in student learning motivation after using the chemistry e-module based on Guided Inquiry Learning. Data were obtained from observation, interviews and distribution of motivation questionnaires. The development model used was 4-D, but only the define, design and development stages were implemented. The subjects of the e-module trial were 26 students of class XI MA Almuhtadi. This study used quantitative descriptive analysis and also inferential analysis. The conclusions in this study (1) the validity of the developed e-module obtained an average score presentation of 88.53% with very valid criteria, which means that the e-module is suitable for use in the learning process and (2) the acid-base e-module based on Guided Inquiry Learning that was developed can increase student learning motivation.